2014
DOI: 10.1021/sb5002533
|View full text |Cite
|
Sign up to set email alerts
|

Synthetic Tunable Amplifying Buffer Circuit in E. coli

Abstract: While predictable design of a genetic circuit's output is a major goal of synthetic biology, it remains a significant challenge because DNA binding sites in the cell affect the concentration of available transcription factors (TF). To mitigate this problem, we propose to use a TF that results from the (reversible) phosphorylation of protein substrate as a circuit's output. We demonstrate that by comparatively increasing the amounts of substrate and phosphatase, the TF concentration becomes robust to the presen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
52
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
4
3
2

Relationship

7
2

Authors

Journals

citations
Cited by 46 publications
(57 citation statements)
references
References 43 publications
5
52
0
Order By: Relevance
“…A number of ways have been proposed to implement such a mechanism within an insulation device [94]. One implementation that was experimentally realized and validated uses a covalent modification cycle as shown in figure 6c [101]. Here, the input amplification G is realized by having a sufficiently large reservoir of inactive protein y in , which upon presentation of the input u is turned into the active output y.…”
Section: Explicit High-gain Negative Feedback To Design Insulation Dementioning
confidence: 99%
“…A number of ways have been proposed to implement such a mechanism within an insulation device [94]. One implementation that was experimentally realized and validated uses a covalent modification cycle as shown in figure 6c [101]. Here, the input amplification G is realized by having a sufficiently large reservoir of inactive protein y in , which upon presentation of the input u is turned into the active output y.…”
Section: Explicit High-gain Negative Feedback To Design Insulation Dementioning
confidence: 99%
“…The output is thus made independent of the presence of load; however, such a device slows down the dynamics of the input. This tradeoff was theoretically characterized in [9] and experimentally verified using a NRI-NRI * PD cycle [8]. The results of [10] suggest that this tradeoff may be overcome by using multiple stages of PD cycles.…”
Section: Introductionmentioning
confidence: 90%
“…A single phosphorylation-dephosphorylation (PD) cycle has been theoretically [6] and experimentally [7], [8] shown to behave as an insulation device due to a high-gain feedback mechanism. In these works, the total substrate and phosphatase concentration of the cycle is increased to attenuate the effect of retroactivity on the output due to the presence of load.…”
Section: Introductionmentioning
confidence: 99%
“…When the demand for the output protein y increases due to load, the large inlet flux quickly generates more y, while the large outlet flux guarantees that no more y than required to track the concentration of the input u is generated. This system has been implemented using the NRI/NRII TCS system of E. coli, in which the authors showed that increased phosphatase and substrate amounts make, as predicted from theory, the system's response independent of load [41]. However, the authors also showed that increasing these amounts make the temporal response of the device substantially slower.…”
Section: Modularity Of Functional Modules: the E↵ects Of Loadsmentioning
confidence: 99%